Impact of Supply Chain Integration on Business Performance: A Review - Manik, Donald; Sinulingga, Sukaria; Ishak, Aulia (Jurnal Sistem Teknik Industri, 2022)
Supply Chain method approach has become a resource for companies to build a sustainable competitive advantage in this complex and volatile competitive environment. Numerous recent literature studies on supply. However, comprehensive analysis, clearly identifying the supply chain relationships used and finding the impact of this relationship on supply chain performance are still lacking. Therefore, this research has the main objective to review past studies on the implementation of supply chain in SMEs, as well as to research the literature to analyze how SMEs have implemented supply chain management approaches. To understand the role of supply chains in SMEs conducted a comprehensive literature review, which resulted in the identification and analysis of 20 high quality international journal articles, published between 2017 and 2021 in English. Based on the findings from this literature review, there are methods or frameworks that can be used by researchers to understand the implementation of Supply Chain Integration in business that can improve performance, efficiency, added customer value, or even competitive advantage. Then, the researcher realizes the need to conduct a literature review to see new developments and findings that have appeared in previous studies. The result is a detailed analysis of the main findings and insights obtained.